The Relationship Between Self-Efficacy and Physical Education Learning Outcomes in Elementary School - Moh. Egy Pratama; Dian Budiana; Ricky Wibowo (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This research is based on the absence of research related to self-efficacy with physical education learning outcomes in elementary schools. Learning outcomes are the gains achieved at the end of learning. Self-efficacy is one of the many factors that affect learning outcomes. In this study, researchers aimed to determine the correlation between self-efficacy and physical education learning outcomes. This research was conducted at SDN 032 Tilil Bandung with a total of 101 respondents. The instrument used, namely the General Self Efficacy Scale (GSES). The results of this study, namely there is a correlation evidenced by Sig. 0.001 <0.05 with low strength (r=0.335). This study shows that self-efficacy contributes to influencing learning outcomes with a coefficient of determination of 10.6% (r2 = 0.106). That way the results of this study that self-efficacy is one of the factors that have a relationship with physical education learning outcomes but there are still other variables that affect learning outcomes.